Output and inflation responses to credit shocks: are there threshold effects in the euro area? - Alessandro Calza; Jo\~ao Sousa (European Central Bank (ECB), 2005)
This paper investigates whether output and inflation respond asymmetrically to credit shocks in the euro area. The methodology, based on a non-linear VAR system, follows work by Balke (2000) for the US. The results reveal evidence of threshold effects related to credit conditions in the economy. Consistent with this finding, the impulse responses show some signs of asymmetric responses over the lending cycle.
Keywords: E51; C15; C32; 330; asymmetric shocks; credit; euro area; non-linearities; Kredit; Schock; Zeitreihenanalyse; VAR-Modell; Bruttoinlandsprodukt; Eurozone; EU-Staaten